2020
DOI: 10.3390/antiox9080744
|View full text |Cite
|
Sign up to set email alerts
|

Gd-Complex of a Rosmarinic Acid Conjugate as an Anti-Inflammatory Theranostic Agent via Reactive Oxygen Species Scavenging

Abstract: Rosmarinic acid (RosA), an important polyphenol, is known for its antioxidant and anti-inflammatory activities. However, its application in theranostics has been rarely reported. Therefore, a new single-molecule anti-inflammatory theranostic compound containing RosA would be of great interest. A gadolinium (Gd) complex of 1,4,7,10-tetraazacyclododecane-1,4,7-trisacetic acid (DO3A) and RosA (Gd(DO3A-RosA)(H2O)) was synthesized and examined for use as a single-molecule theranostic agent. Its kinetic stability is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…DO3A-flavonoid is designed to maintain active sites for antioxidant effects and increase synthesis efficiency ( Figure 1 ). The ester and ether bonds have a lower binding strength compared to the widely used amide bonds [ 16 , 34 ], and ester bonds can be decomposed into enzymes such as esterase [ 53 ]. Based on the ester bond, the DO3A and flavonoid portions are protected in decomposition because they have a large structure that is difficult to act on esterase [ 54 ], and the stability of DO3A-flavonoid was verified in experiments compared with used contrast agents ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DO3A-flavonoid is designed to maintain active sites for antioxidant effects and increase synthesis efficiency ( Figure 1 ). The ester and ether bonds have a lower binding strength compared to the widely used amide bonds [ 16 , 34 ], and ester bonds can be decomposed into enzymes such as esterase [ 53 ]. Based on the ester bond, the DO3A and flavonoid portions are protected in decomposition because they have a large structure that is difficult to act on esterase [ 54 ], and the stability of DO3A-flavonoid was verified in experiments compared with used contrast agents ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Samples used for relaxivity determinations were prepared at five concentrations (0.0625, 0.125, 0.25, 0.5, and 1 mM) in deionized water, phosphate-buffered saline (PBS), or 0.67 mM human serum albumin (HSA) solution [ 16 ]. The three synthesized Gd complexes and various commercial contrast agents Gd-BT-DO3A (Gadovist ® ), Gd-DTPA-EOB (Primovist ® ), Gd-DTPA-BOPTA (MultiHance ® ), Gd-DTPA (Magnevist ® ), and Gd-DOTA (Dotarem ® )) were measured together using a Signa Architect 3.0 T system (128 MHz, GE Healthcare, Milwaukee, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the analysis of protein expression changes, C2C12 cells (5 × 10 3 cells/dish) were inoculated into a 60-mm culture dish. After inducing differentiation for 3 days, palmitate acid or/and drugs were added to the growth medium and incubated for 24 h. Cells were harvested, and protein extraction and Western blotting were performed as described in a previous study [ 54 ]. Membranes were incubated with the following diluted primary antibodies: COX-2 (1:2000, Cell Signaling Technologies, Beverly, MA, USA, Catalog No.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that RA exhibits strong anti-oxidant capacity in biological systems by scavenging free radical and reactive oxygen species (Ghorbani et al 2019 ; Kim et al 2020a ). Recently, Sadeghi et al ( 2020 ) investigated the impact of RA on lipopolysaccharide-induced oxidative damage and inflammation in peripheral blood mononuclear cells.…”
Section: Pharmacological Properties Of Ramentioning
confidence: 99%